Rox, a Rifamycin Resistance Enzyme with an Unprecedented Mechanism of Action. Issue 4 (19th April 2018) - Koteva, Kalinka; Cox, Georgina; Kelso, Jayne K.; Surette, Matthew D.; Zubyk, Haley L.; Ejim, Linda; Stogios, Peter; Savchenko, Alexei; Sørensen, Dan; Wright, Gerard D.
Summary: Rifamycin monooxygenases (Rox) are present in a variety of environmental bacteria and are associated with decomposition of the clinically utilized antibiotic rifampin. Here we report the structure and function of a drug-inducible rox gene from Streptomyces venezuelae, which encodes a class A flavoprotein monooxygenase that inactivates a broad range of rifamycin antibiotics. Our findings describe a mechanism of rifamycin inactivation initiated by monooxygenation of the 2-position of the naphthyl group, which subsequently results in ring opening and linearization of the antibiotic. The result is an antibiotic that no longer adopts the basket-like structure essential for binding to the RNA exit tunnel of the target RpoB, thereby providing the molecular logic of resistance. This unique mechanism of enzymatic inactivation underpins the broad spectrum of rifamycin resistance mediated by Rox enzymes and presents a new antibiotic resistance mechanism not yet seen in microbial antibiotic detoxification. Graphical Abstract: Highlights: Unique inducible mechanism of antibiotic resistance Class A flavoprotein monooxygenases ROX-mediated monooxygenation causes rifamycin linearization Abstract : The ROX family of monooxygenases mediates resistance to rifamycin antibiotics. Koteva, Cox, Kelso et al. report the structural and biochemical characterization of these enzymes, revealing that monooxygenation causes linearization of the antibiotic. This results in an altered conformation that inhibits the ability of the antibiotic to bind to its target, RNA polymerase.